Synthesis of silver nanoparticles by Lactobaciluus acidophilus 01 strain and evaluation of its in vitro genomic DNA toxicity - Namasivayam, S. Karthick Raja; Gnanendra, E. Kumar; Reepika, R. (Nano-Micro Letters, 2010)
Silver nanoparticles synthesized by dried biomass of Lactobaciluus acidophilus 01 strain was evaluated against toxicity of genomic DNA isolated from bacteria (E. coli) fungi (Beauveria bassiana) algae (Seenedesmus acutus) and human blood adopting standard condition was discussed in the present study. Synthesized silver nanoparticles were characterized by UV-Vis spectroscopy and SEM. The UV-Vis spectroscopy revealed the formation of silver nanoparticles by yielding the typical silver plasmon absorption maxima at 430 nm and SEM micrograph indicates the uniform spherical particles within the size range of 45∼60 nm. The energy dispersive X-ray spectroscopy (EDX) of the nanoparticle confirmed the presence of elemental silver signal as strong peak. The above synthesized silver nanoparticles didn’t cause any toxic effect on all the tested genomic DNA at all tested concentrations which reveals nil genomic nanoparticles induced toxicity.